Pericardial fat burden on ECG-gated noncontrast CT in asymptomatic patients who subsequently experience adverse cardiovascular events on 4-year follow-up: A case-control study - Cheng, Victor Y. (2010)
BACKGROUND: Pericardial fat volume (PFV) and thoracic fat volume (TFV) can be routinely measured from noncontrast CT (NCT) performed for calculating coronary calcium score (CCS) and may predict major adverse cardiovascular event (MACE) risk. METHODS: From a registry of 2751 asymptomatic patients without known CAD and 4-year follow-up for MACE (cardiac death, myocardial infarction, stroke, late revascularization) after NCT, we compared 58 patients with MACE (“EVENTS”) to 174 same-sex event-free controls matched by a propensity score to account for age, risk factors, and CCS. TFV was automatically calculated, and PFV was calculated with manual assistance in defining the pericardial contour, within which fat voxels were automatically identified. Independent relationships of PFV and TFV to MACE were evaluated using conditional multivariable logistic regression. RESULTS: EVENTS had higher mean PFV (101.8±49.2 cm(3) vs. 84.9±37.7 cm(3), p=0.007) and TFV (204.7±90.3 cm(3) vs. 177±80.3 cm(3), p=0.029) and higher frequencies of PFV>125 cm(3) (33% vs. 14%, p=0.002) and TFV>250 cm(3) (31% vs. 17%, p=0.025). After adjusting for Framingham Risk Score, CCS, and body-mass-index, PFV and TFV were significantly associated with MACE (odds ratio (OR) 1.74, 95%CI 1.03–2.95 for each doubling of PFV; OR 1.78, 95%CI 1.01–3.14 for TFV). Areas-under-the-curve from receiver operating characteristic analyses showed a trend of improved MACE prediction when PFV was added to FRS and CCS (0.73 vs 0.68, p=0.058). Addition of PFV, but not TFV, to FRS and CCS improved estimated specificity (0.72 vs 0.66, p=0.008) and overall accuracy (0.70 vs 0.65, p=0.009) in predicting MACE. CONCLUSION: Asymptomatic patients who experience MACE exhibit greater PFV on pre-MACE NCT when compared to event-free controls with similar cardiovascular risk profiles. Our preliminary findings suggest that PFV may help improve prediction of MACE.